CREDIT RATING AGENCIES AND THEIR EFFECTS: AN ANALYSIS ON BALKAN COUNTRIES - Yıldırım, Nuh Ekrem; Üre, Salim; Karaköy, Çağatay (Journal of process management and new technologies, 2021)
The financial structure in the world has become more complex with the increase in global capital movements. For this reason, credit rating agencies have emerged as an important component of the financial structure. Standard and Poors, Moody’s and Fitch are the three most important companies in this market. The grades given by these institutions highly affect the economic situation of the countries. In this study, information is given about credit rating agencies and it is aimed to measure the effect of the points given to countries by Standard and Poors, Moody’s and Fitch, which are the most important of these institutions, on the economy. For this purpose, the effect of credit scores on the economic growth of Balkan countries except Kosovo was analyzed using panel data analysis method. In addition, unemployment, inflation, current account balance and budget balance data were included in the analysis. The findings obtained show that credit scores have an effect on the economic growth of countries.